Evaluación del efecto de la adición de un microencapsulado de aceite de orégano (Origanum vulgare L.) en el retardo de la oxidación lipídica y aceptación sensorial de una salsa tipo mayonesa durante su almacenamiento acelerado. - Garay Freire, Anabel Cristina (2021)
The objective of the present research was to evaluate the influence of oregano oil microencapsulate (Origanum vulgare L.) addition as a natural antioxidant on mayonnaise stability. (M.p) for standard sample antioxidant EDTA, (PC1) for the maximum concentration of oregano oil microencapsulate and (PC2) for the minimum concentration of oregano oil microencapsulate was used. Three 10-liter batches of mayonnaise were developed. Lot 1 (M.p) EDTA synthetic antioxidant was added 0.07g / kg according to NTE 2235 (2010). Lot 2 PC1 added 4.44g of oregano microencapsulate. Lot 3 PC2 1.42g microencapsulated oregano. The mayonnaises were stored at 35ºC, 45ºC and 55ºC for 35 days on accelerated storage, to determine physical, chemical, sensory and organoleptic properties changes at the beginning and at the end. At this part is observed that microencapsulate addition delayed lipid oxidation process of the mayonnaises during 35 days at given temperatures. Concluding that PC2 mayonnaise demonstrated better stability during accelerated storage at all temperatures. The research period was since September 2020 to March 2021 at microbiology laboratories of Agroindustries career of Agricultural Sciences and Natural Resources Faculty at Technical University of Cotopaxi.